In Vitro Screening of Tomato Cultivars against Cadmium Tolerance in Iraq - Qusay Abdulhamza Muttaleb; Ahmed Falih Shamukh; Roaa Wahhab Mohammed Khafaji; Kotsareva Nadezhda Victorovna (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Cadmium (Cd) is a heavy metal, highly toxic, soluble in water, and easily taken up by plants. Consequently, it produces abnormal growth and disturbs the metabolism of plants. The present study consists of an in vitro study of nine tomato cultivars in comparison to the application of Cd to know their effect on different growth parameters of tomato cultivars, including seed germination, mean generation time (MGT), shoot length, and root length (cm). All cultivars were scored based on a systematic procedure. Results showed that the Cd treatment influenced the germination percentage of tomato cultivars. After Cd treatment, a maximum and a minimum germination percentage of 62.67±2.89 and 25.00±5.00 were observed for T-59 and Tmt-9, respectively. However, the most susceptible cultivars were recorded as Tmt-9. The shortest MGT was recorded in T-59 (4.04±2.57 days) and the longest in Tmt-9 (10.12±2.61 days). The heavy impact of Cd was recorded on shoot height; meanwhile, T-59 produced a maximum shoot height of 7.47±0.26 cm and showed the lowest Cd inhibition. The root height in Tmt-9 was 6.00±1.01 cm to 1.85±0.16 cm; thus, showed high influence with Cd application. After Cd application, roots less inhibition of 7.10±0.62 cm was recorded. Based on the ranking score, T-59 ranked first with 16.00 points for seed germination, MGT, shoot length, and root length. Based on the results, it is recommended to sow the T-59 tomato variety that proved less influenced by Cd.